(Pós) ensino remoto: os recursos tecnológicos digitais nos processos de escolarização - Colpo, Alexandra Marin (2023)
This dissertation is linked to the Center for Studies and Research on Schooling and Inclusion (NUEPEI) and the Postgraduate Program in Public Policies and Educational Management, at the Federal University of Santa Maria (UFSM), in the Research Line LP2 – Pedagogical Management and Educational Contexts. The research problem is based on the following question: How do the digital technological resources used during Remote Teaching have an impact on the constitution of pedagogical practices when returning to face-to-face classes? The general objective was to identify and analyze the use of digital technological resources in pedagogical practices (Post) Remote Teaching. Specific objectives: characterize pedagogical practices that use digital technological resources and reflect on the contributions of digital technological resources used for teaching work. The research product resulted in a digital Flipbook, with written and photographic documents about teaching situations, planned by educators, using digital technological resources. Methodologically, the research was based on a qualitative research approach, inspired by the cartographic method, which considers the construction processes of the research itself, as well as the subjects involved. The study was developed in a school in the Municipal Education Network of Santa Maria/ RS, which serves students from Early Childhood Education to the 5th year of Elementary School and has as collaborators four (4) teachers from Elementary School Early Years classes and a teacher who works in IT. As a recording procedure, a script was used to prepare a narrative text, made available via Google Drive, in addition to a file for including photographic records, which illustrated the work propositions. In a second moment, a conversation was held, where actions that are being developed with the use of digital technological resources were shared, an important moment of exchange and enrichment for the redefinition of the Teaching processes in this institution. The analyzes were produced considering the theoretical concepts of the authors such as: Maturana (1994, 2001, 2014), Maturana and Varela (2001); Philippe Meirieu (1998, 2006); Maria José Esteves de Vasconcellos (2018); Nilze Maria Campos Pellanda (2009); Moran, Masetto and Behrens (2013), and contributions from the literature review over a period of time from 2020 to 2022, through a selection of productions related to the theme. The data were analyzed based on two analytical dimensions: the relationships between pedagogical practices and digital technological resources; and the contributions of digital technological resources to teaching work. As a conclusion of the research, there is an investment in the power of using technology as a resource to be used and offering different ways of learning to students. Digital inclusion appears as a way to ensure that all students have adequate access to technology and training to use it effectively and responsibly. The need to invest in the continued training of teachers is emphasized, as well as guaranteeing educational IT teachers, who are essential. The contribution of technology to educational practices stands out as the experiences that are provided to students.